Myth and Authority : Giambattista Vico's Early Modern Critique of Aristocratic Sovereignty. - Bertland, Alexander U. (Redwood City : State University of New York Press, 2022)
Argues that Giambattista Vico's early modern account of Roman mythology was a sophisticated attempt to present an epistemological and political critique of the aristocratic way of conceiving the world.
7. Poetic Wisdom and Class Conflict -- Mars, God of Defense -- The Basis of the Class Division -- Naked Venus -- Minerva and Solon -- 8. Is Vico Right? -- Vico and Early Modern Thought -- Vico and Contemporary Italian Thought -- The Consolation of Philosophy -- Notes -- Bibliography -- Index
Description based upon print version of record.
JSTOR
Keywords: Vico, Giambattista, -- 1668-1744; Political science -- Philosophy; Despotism -- Philosophy; Despotisme -- Philosophie